2000
DOI: 10.1016/s0022-5347(05)67711-7
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Predictors of Prostate Cancer on Repeat Prostate Biopsy: A Prospective Study of 1,051 Men

Abstract: At least 10% of patients with negative initial prostatic biopsy results will be diagnosed with prostate cancer on repeat biopsy. Percent free PSA and transition zone PSA density enhance the specificity of PSA testing compared to total PSA or PSA density when determining which patients should undergo repeat biopsy. Repeat biopsy should be performed in patients with percent free PSA less than 30% or transition zone PSA density 0.26 ng./ml./cc or greater. In our study percent free PSA was the most accurate predic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
164
2
6

Year Published

2002
2002
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(184 citation statements)
references
References 31 publications
12
164
2
6
Order By: Relevance
“…2,15 In contrast, minor complications are frequent, with 60-79%. 5,16 Most of these complications do not require any intervention and are selflimiting. However, it is essential to have a clear understanding of the true morbidity of this procedure to counsel the patient accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…2,15 In contrast, minor complications are frequent, with 60-79%. 5,16 Most of these complications do not require any intervention and are selflimiting. However, it is essential to have a clear understanding of the true morbidity of this procedure to counsel the patient accordingly.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, several other prostate cancer markers including percent free PSA, PSA velocity and PSAD of the transition zone have been suggested as highly sensitive and specific for prostate cancer. [19][20][21][22] These values were unavailable in these data, but addition of these factors to the nomogram may have further improved its diagnostic accuracy. Additionally, validation of our nomogram in the same cohort in which it was developed may be problematic with regard to overfit bias, and the need for external validation is clear.…”
Section: Discussionmentioning
confidence: 99%
“…15 indirectly demonstrated the problem of not performing laterally directed biopsies. In their study of 1051 men, eight biopsies were obtained including six of the sextant format and two of the TZ.…”
Section: Biopsy Techniquementioning
confidence: 99%
“…While initial evaluation of this issue revealed an increased false-negative rate in biopsies for those with increased volumes, further studies have yielded mixed results. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] These studies have also addressed the need for extended biopsy schemas in larger volume prostates. Ung et al 18 demonstrated no statistical difference in CaP detection rates in patients undergoing increased numbers of biopsies beyond nine cores.…”
Section: Biopsy Techniquementioning
confidence: 99%